The Effect of Video-Based Educational Media on Pregnant Women’s Knowledge of Pregnancy Danger Sign - Elva Febri Ashari; Agrianingsih Oktaviana Hadi (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2026)
Pregnancy danger signs are important indicators that require immediate medical attention to prevent maternal and fetal complications. However, limited knowledge among pregnant women regarding these warning signs remains a significant public health concern. This study aimed to analyze the effect of video-based educational media on the knowledge of pregnant women about pregnancy danger signs. The research employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The study involved pregnant women attending antenatal care services at a maternal health facility. Data were collected using structured questionnaires administered before and after the educational intervention. The intervention consisted of health education delivered through an educational video explaining the types, symptoms, and prevention of pregnancy danger signs. Data were analyzed using statistical tests to compare pretest and posttest scores. The results showed a significant increase in the participants’ knowledge after receiving the video-based education, indicating that audiovisual media effectively improved understanding and information retention. The findings suggest that educational videos can serve as an innovative and accessible health promotion strategy to enhance maternal awareness and encourage timely healthcare-seeking behavior during pregnancy.